MOTIVASI IBU HAMIL DALAM MENGKONSUMSI MAKANAN YANG MENGANDUNG ASAM FOLAT DI DESA KEBONAGUNG KECAMATAN PORONG KABUPATEN SIDOARJO - Lida Khalimatus Sa’diya (Bahasa Indonesia, 2015)
Folic acid is very important especially in the early days of pregnancy, because at that time the nervous system of a baby is being formed. Folic acid deficiency causes babies born with cleft lip, babies born with low weight, down's syndrome, and miscarriage. The purpose of this study was to determine the motivation of pregnant women to consume folic acid in the Village Kebonagung Porong Sidoarjo. This research is a descriptive study. Population in this study sample of 41 respondents who used as many as 41 respondents drawn with total sampling technique. After the analysis of data collected by the data editing, coding, scoring, tabulating. The results motivate pregnant women to consume folic acid in the Village Kebonagung Porong Sidoarjo in 2013 showed that of the 41 respondents largely motivated weak as many as 20 respondents (48.8%) and the fraction that is strongly motivated by 8 respondents (19.5%) . Weak motivation is manifested in the form of a weak desire to consume folic acid as part of a much-needed nutrients pregnant women in the developing baby. Motivation studies in pregnant women taking folic acid in the Village Kebonagung Porong Sidoarjo in 2013 showed that of the 41 respondents largely motivated weak. That mothers should increase motivation in consuming foods that contain lots of folic acid for the health of the mother and fetus were conceived.